Yield Potential Analysis of Cacao Clones in Various Location in East Kolaka Regency, Southeast Sulawesi - Besse Asriana; Marlina Mustafa; Yolanda Fitria Syahri (Agrotech Journal, 2017)
The Southeast Sulawesi government has designated Kolaka Timur as one of the cocoa production centers in Southeast Sulawesi. One of the successes of the superior seed assembly business depends on the availability of complete and accurate information about the potential of cocoa to be chosen as elders for subsequent development, so that yield analysis and early selection in the analysis of genetic diversity of smallholder cocoa have been developed in that location. This research was carried out using the Split-Plot Design (RPT). Sampling was carried out in 3 main locations (L) with an area of ± 2 ha, in each of the main locations divided into three plots (P) namely plots one Sulawesi 2 clones, plots two local clones and plots 3 MCC02 clones. A sampling of cacao leaves and fruit was taken as many as 30 samples with three replications per location. The results showed that cocoa which has the potential for good yields to be developed in the East Kolaka Regency based on the analysis of the component production of dry seed weight was the MCC02 cocoa clone with an average of 35.33 grams of fruit (L2P3) respectively. The different locations show different levels of Cacao yield and adaptation